Policy pathways for advancing climate resilient irrigation in Kenya - Jennings, Stewart; Challinor, Andrew; Jalango, Dorcas; Chilambe, Pedro; Binge, Brenda (2025)
Climate change is causing the frequency and severity of heat waves, droughts and floods to increase in many parts of sub-Saharan Africa. This necessitates an improved understanding of the potential impacts of climate change on food systems and how we might adapt to avoid worsening food and nutrition insecurity. We assess the potential benefits of planned irrigation expansion in Kenya for delivering climate-resilient nutrition security by 2050. Irrigation can form part of a climate-smart future alongside other adaptation measures that increase agricultural production. Although irrigation can turn food production losses into gains, irrigation alone will not improve nutrition security. Without broader adaptation measures that improve crop yields, and expanding diversified agricultural areas, nutrient deficiencies remain (e.g. calcium, iron and zinc). Irrigation expansion therefore needs to prioritize the right crops to meet all nutrient requirements by 2050 – targeting vegetable production – to avoid increasing the reliance on food imports to meet demands.